2021
DOI: 10.3390/molecules26247550
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead by Merlinoite Prepared from Sugarcane Bagasse Ash and Kaolin: Synthesis, Isotherm, Kinetic, and Thermodynamic Studies

Abstract: This study introduces a merlinoite synthesized from sugarcane bagasse ash (SBA) and kaolin and evaluates its application as an adsorbent to remove lead from wastewater. The synthesis was performed via the hydrothermal method, and optimal conditions were determined. The adsorption of Pb by merlinoite was also optimized. Determination of the Pb2+ remaining in the aqueous solution was determined by atomic absorption spectroscopy (AAS). Adsorption isotherms were mainly studied using the Langmuir and Freundlich mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, the incomplete removal of the contaminants and the generation of secondary pollutants are the main drawbacks of these conventional methods. 23 25 Interestingly, a semiconducting photocatalytic route is a promising technique for complete removal of the toxic organic pollutants. 5 , 16 , 17 Basically, the commercially available TiO 2 is a UV-active photocatalyst with low photoactivity under natural sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incomplete removal of the contaminants and the generation of secondary pollutants are the main drawbacks of these conventional methods. 23 25 Interestingly, a semiconducting photocatalytic route is a promising technique for complete removal of the toxic organic pollutants. 5 , 16 , 17 Basically, the commercially available TiO 2 is a UV-active photocatalyst with low photoactivity under natural sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques including adsorption were used to treat the pollutants in wastewater. However, the incomplete removal of the contaminants and the generation of secondary pollutants are the main drawbacks of these conventional methods. Interestingly, a semiconducting photocatalytic route is a promising technique for complete removal of the toxic organic pollutants. ,, Basically, the commercially available TiO 2 is a UV-active photocatalyst with low photoactivity under natural sunlight. The ZnO photocatalyst has gained much attention because it shows excellent transport property, is inexpensive, and has a versatile morphology. In addition, based on our previous studies, controlled synthesis can be performed very easily for the creation of ZnO with high performance and also with a low cost of production. ,, Therefore, in comparison to TiO 2 , ZnO is much cheaper and very easy to synthesize controllably. Nevertheless, low sunlight performance and occurrence of the photocorrosion are the main drawbacks influencing the practical application of ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that various techniques have been applied for the removal of toxic contaminants in wastewater. However, major disadvantages in comparing the incomplete removal of the contaminants and the generation of secondary harmful pollutants are detected [ 15 , 16 , 17 ]. Alternatively, to reach the sustainable development goals, photocatalytic treatment has been used for the complete degradation of the organic contaminants [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%